Microclimate in Rooms Equipped with Decentralized Façade Ventilation Device - Ewa Zender-Świercz (Atmosphere, 2020)
Many building are characterized by insufficient air exchange, which may result in the symptoms of sick building syndrome (SBS). A large number of existing buildings are equipped with natural ventilation, whose work is disturbed by activities going to energy-saving. The thermomodernization activities are about mounting new sealed windows and laying thermal isolation, which reduces the amount of infiltrating/exfiltrating air. In many cases, the mechanical ventilation cannot be used due to a lack of a place in building or architectural and construction requirements. One of the solutions to improve the indoor microclimate is the decentralized façade ventilation. In the article, the internal air parameters in an office room equipped with decentralized façade ventilation device were analyzed. The room was equipped with a decentralized façade unit, which cyclically supplied and removed air from the room. The time of the supply/exhaust was changed to 2 min, 4 min, and 10 min. The temperature and the humidity of the indoor air and the outdoor air and the concentration of carbon dioxide inside the room were measured. The analysis showed that despite the lack of a heater in the device, the air temperature in the workplace and in the central point of the room was in the range of 20–22 °C. The air humidity was in the range of 27–43%.